Exploring the Impact of Monopolistic Practices on the Nigerian Economy: An Islamic Perspective - Nurudeen Hanafi Olushola (Universitas Muhammadiyah Yogyakarta, 2024)
The economy is the backbone of the success of any country. A failure in its domain is equivalent to failure in other aspects. Nigeria, the most populous country in Africa, which has been considered a land of vast economic potential, is still struggling to actualize this prospect due to some imperfections. Monopoly hugely contributes to market imperfection, and its effects can be constraints on economic growth. The issue had arisen since the advent of Islam, whereby it was used as a strategy to maximize profit. The Islamic system believes in the co-existence of an economic public sector along with the private sector. Though Islam frowns at any market imperfection that can lead to paroxysms of increasing prices for both suppliers and consumers, it also pinpoints regulatory measures. The study, therefore, adopted a qualitative method, which was used to review related and relevant literature on the concept of monopoly, and interviews were also conducted to gather information on the practice and effect of monopoly. The paper revealed that among the regulatory measures used to control this market imperfection was Ḥisbah. The study exposed that killing the sense of competitiveness in the market is the most atrocious effect of monopoly on the Nigerian economy. The paper also found that the Nigerian economy can regain its breath and fame if these measures can be applied to control the juggernauts' engineering in the market either by halting the competitive market, hoarding, or proportioning scarcity. The study recommended that the government should play its role as an overall investigating force over the prices dictated by the public and private sectors.